Non-free iterative differential modules - Maurischat, Andreas (ACM Communications in computer algebra, 2017)
In [7] we established a Picard-Vessiot theory over differentially simple rings which may not be fields. Differential modules over such rings were proven to be locally free but don't have to be free as modules. In this article, we give a family of examples of non-free differential modules, and compute Picard-Vessiot rings as well as Galois groups for them.
Gesehen am 20.02.2019